Efl Students’ Engagement in Authentic Materials-Based Online Jigsaw Reading Activity - Budiharti, Silvya; Saefullah, Hilmansyah; Mobit, Mobit (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
Though many previous studies have examined about authentic materials or jigsaw activity for reading classroom, it is still lack of study about integrating the authentic materials in a virtual reading classroom context. To fill this gap, this case study investigated about English as a Foreign Language (EFL) students’ engagement in virtual jigsaw reading with authentic texts. Drawing data from the observation and interview of four volunteer of secondary students, it was found that the students participated and interacted with others during the activity. In addition, the students performed self regulation as they divided the duties in the group. Finally, the students showed their enjoyment and interests in the reading activity.